Organization Of Tourism Services In Uzbekistan Based On The Combination Of National Styles And Modern Innovations - B. F. Botirov; J. Usmonov; R. I. Ablyakimova (International Scientific and Current Research Conferences, 2021)
The article is devoted to the dynamic development of innovative activities in the current tourism industry in Uzbekistan and the study of related infrastructure in terms of innovation, as well as practical recommendations for the scientific development of opportunities for innovative development of road tourism and tourism infrastructure in our country. Young tourists also have the opportunity to get acquainted with rural life, nature and traditions through the organization of "Tourist Houses".